The hangover: The cost of minimum alcohol pricing in Scotland - John C. Duffy; Christopher Snowdon; Mark Tovey (Institute of Economic Affairs (IEA), 2022)
Minimum unit pricing (MUP) sets a floor price on a unit of alcohol to prevent the sale of 'cheap' drinks, with the aim of reducing alcohol related harm. MUP was introduced in Scotland on 1 May 2018 at 50p per unit. This study estimates the financial cost to consumers in the four years since implementation.Using sales data from the Public Health Scotland evaluation, we compare off-trade alcohol sales in Scotland post-implementation with a counterfactual based on sales figures from England and Wales.Extrapolated over the four years of implementation, we estimate that MUP has cost Scottish consumers 270 million. This amounts to 59.39 per adult or 71.12 per drinker. This is significantly more than was projected in models prior to implementation.There is little evidence of health and social benefits to offset this cost. Most indicators related to alcohol-related health, crime and employment have remained similar or worsened since MUP was implemented, although many of the projected benefits were so small it would be difficult to identify them in aggregate data.
Keywords: 330; Alcohol; price; alcohol policy; private consumption; Scotland; Alkohol; Preis; Alkoholpolitik; Privater Konsum; Schottland